MicroRNAs are a key factor in the globalization of tumor-host relationships - Chekhun, V.F. (PH Akademperiodyka, 2023)
Summary. A new round of molecular oncology development in the post-genomic era significantly changes the conventional understanding of the nature and origin of the malignant process. Increasingly, fundamental phenomena are emerging that change the “canonical” views of the dominant role of gene mutations that contribute to the uncontrolled proliferation and emergence of heterogeneous malignant cells. Recent numerous studies have shown that significant variability in the initiation, proliferation and control of the apoptotic program of tumor cells is due to numerous epigenetic processes, including the level of expression of microRNAs (miRNAs). This paper reviews the literature data and presents the results of own research in which miRNAs have been found to form a molecular phenotype for malignancy. Their role as a “conductor” of the functioning of a genetic-epigenetic orchestra that coordinates various aspects of malignancy has been suggested. MiRNAs have been shown to be an active participant in balancing mechanisms in the development of controversial processes in breast cancer cell lines of varying degrees of malignancy. The analysis of the literature data and the own studies of the expression profile of only a few miRNAs suggests that scientists and clinicians have received a new marker and a target that simultaneously plays the role of an active insider in both the oncogene-oncosuppressor relationship and in the globalization of this process at the tumor-host level. Further investigation of the “alarm” marker in this network will allow to reconsider the molecular genetic classification of neoplastic disease, which will provide the development of a new strategy for cancer therapy.